Perbandingan Faktor-Faktor yang Mempengaruhi Pengetahuan Tentang Asi Ekslusif Antara Ibu yang Melahirkan di BPM Dengan Puskesmas - Heriza Syam; Jehanara Jehanara; Nurdjasmi Nurdjasmi (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2019)
Mother's knowledge is one factor in the success of exclusive breastfeeding. Research in Ghana (2008), 1.3 million infant deaths can be prevented by the provision of breast milk (ASI) in infants from the first day of birth until under the age of 5 years. If breastfeeding starts in the first 1 hour after birth, This figure rises to 22% from 16%,. This study aims to determine the differences in knowledge about Exclusive Breastfeeding and the factors that influence it in post partum mothers in BPM with Puskesmas in the East Jakarta area. Research Design: Observational analytic study with the approach used is cross sectional. The results showed that there were significant differences (P = 0.001) between the place of labor and the knowledge of nursing mothers. Mothers who gave birth at the Good Knowledge Midwife Practice (PMB) were 78.6%, while those in the Puskesmas were only 38.5%. Characteristics of respondents related to knowledge of post partum mothers about breastfeeding were Education (P 0.01), Economy, (P 0.000) and ethnicity (P 0.019). Factors-education, economy and ethnicity influence mother's knowledge about exclusive breastfeeding. Place of birth in the Independent Practice Midwives have the opportunity to increase knowledge of exclusive breastfeeding 3 times compared to the knowledge of mothers who give birth at the Puskesmas after controlled by the Education variable.